Evolution and Moral Diversity - Tim Dean (Baltic International Yearbook of Cognition, Logic and Communication, 2012)
If humans have an evolved moral psychology, then we should not expect it to function in an identical way between individuals. Instead, we should expect a diversity in the function of our moral psychology between individuals that varies along genetic lines, and a corresponding diversity of moral attitudes and moral judgements that emerge from it. This is because there was no one psychological type that would reliably produce adaptive social behaviour in the highly heterogeneous environments in which our minds evolved. As such, there was no single psychological type towards which evolution could gravitate. Instead we evolved a stable polymorphism of psychological types, maintained by frequency-dependent selection, each predisposed towards particular social and moral attitudes and behaviours. This can help explain the existence of moral diversity, particularly intra-cultural moral diversity, and seemingly intractable moral disagreement.